Developing Mystery Box in Teaching Narrative Text for Speaking Class at Junior High School - Silvya Utami; Mukhtarul Anam; Riryn Fatmawaty (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2022)
This research aims to develop a Mystery Box for teaching speaking in narrative text for junior high school students. To improve speaking skills students often face several problems such as lack of confidence when speaking in a foreign language. The main purpose of this research is to help students improve students' speaking skills gradually during teaching and learning activities in the classroom. This study uses Research and Development (R&D) model from Thiagarajan or commonly known as 4D (Four-D). The stage is Define, which is a definition that includes observation and analysis of student needs, then Design which includes product design formats and material selection, then Develop includes product design, validation by experts, revisions, and small-scale to large-scale experiments, the last is Disseminate, namely dissemination product form is a Guidebook. Observation data, interviews, and questionnaires for students used qualitative while the expert validator questionnaires and students' speaking scores used quantitative. There were two experts who tested this product and the participating students were class IX G, IX H, and IX I. The result of the analyzing all the data, according to the experts Mystery Box categorized was very good and most of the students felt enthusiastic in the class. It can be concluded that the Mystery Box is a learning media for helping students to improve students’ speaking skills.